Description of the novel HLA‐DQB1*02:02:01:02 allele in a Spanish individual. (28th December 2015) - Montero‐Martín, G.; Cervera, I.; Teniente‐Serra, A.; Fonolleda, M.; Martinez‐Laso, J.
Abstract: HLA‐DQB1*02:02:01:02 has an intron sequences coming from a combination of DQB1*02:01:01 and DQB1*02:02:01:01 .